A Comparison of Musculo-Articular Stiffness and Maximal Isometric Plantar Flexion and Knee Extension Force in Dancers and Untrained Individuals. Issue 4 (December 2017) - Rice, Paige E.; van Werkhoven, Herman; Dejournette, Denzel J.; Gurchiek, Reed D.; Mackall, John W.; McBride, Jeffrey M.
Dance involves a high volume of aesthetic, stretch-shortening cycle (SSC) actions, which may cause unique adaptations to performance. The strength dancers possess to withstand such frequency of SSCs remains elusive. The extensive training that dancers experience from a young age, however, yields anatomical and strength development that may contrast with that of untrained individuals. Therefore, the purpose of this study was to investigate differences in musculo-articular stiffness and maximal isometric plantar flexion and knee extension force between dancers and untrained individuals. A total of 16 females volunteered to participate in the study (N = 8 dancers; N = 8 untrained individuals). Dancers had a minimum of 10 years of dance experience and were currently training at the collegiate dance level three or more times per week. Untrained individuals had no dance background, nor were they currently involved in any form of regularized physical activity. Al subjects completed a series of lower leg measurements and strength tests. This included a musculo-articular stiffness measurement using a free-oscillation technique, along with maximal isometric plantar flexion (MIP) and maximal isometric knee extension (MIKE) testing. The data indicate that dancers had a significantly greater rate of force development and peak force during MIP and rate of force development during MIKE in comparison to untrained individuals. Dancers also possessed significantly greater musculo-articular stiffness. Hence, the data provide some evidence that involvement in dance can result in greater muscle force generating capacity and musculo-articular stiffness due to the SSC mechanisms involved in dance movements.